Le rôle de l’espace public dans la révolution de Jasmin à Tunis - Emna Khemiri (Projets de Paysage)
In this article, one shall address the Tunisian Revolution of January 14th 2011 from the perspective of the spatial and cultural upheaval it brought. One shall try to describe the difficult genesis of the public space – as a place of debate and of challenging the political, moral, and social order – both in relation to the Arab-Islamic tradition and to the dictatorial regime of Ben Ali. One will also attempt to shed some light on the various shapes of the re-appropriation dynamics of the public spaces by the citizens. One shall focus more particularly on the dialectical nature of this re-appropriation act. In this action, the space works not only as the theatre of the revolution, and gives it the opportunity to become concrete in highly symbolical places – such as the Habib-Bourguiba avenue or the Casbah –, but it is also what is at stake in a struggle: the re-appropriation of an official space such as the Casbah, on the occasion of the various “sit-ins”, provoked a toughening of the revolutionary process.